Carbene-catalyzed enal γ-carbon addition to α-ketophosphonates for enantioselective access to bioactive 2-pyranylphosphonates. Issue 47 (25th May 2018) - Sun, Jun; He, Fangcheng; Wang, Zhongyao; Pan, Dingwu; Zheng, Pengcheng; Mou, Chengli; Jin, Zhichao; Chi, Yonggui Robin
Abstract : A carbene-catalyzed [4+2] reaction of enals and α-ketophosphonates is developed to afford chiral 2-pyranylphosphonates with potential use in plant protection. Abstract : A carbene-catalyzed enantioselective [4+2] cycloaddition reaction between α, β-unsaturated aldehydes and α-ketophosphonates is developed. The reaction affords chiral 2-pyranylphosphonates with excellent enantioselectivities. The optically enriched phosphonate products bear multiple functional groups, including unsaturated lactone and phosphonate moieties that often lead to unique bio-activities. Preliminary studies show that the products from our reactions exhibit anti-bacterial ( X. oryzae pv. oryzae ) and anti-viral (Tobacco Mosaic Virus) activities for potential use in plant protection.